2021
DOI: 10.1016/j.landurbplan.2021.104189
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering landscape preferences: Investigating the roles of familiarity and biome types

Abstract: Although people generally have positive evaluations of natural environments and stimuli, theory and research suggest that certain biomes are more preferable than others. Existing theories often draw on evolutionary ideas and people's familiarity with biome types, with familiarity being the most supported, albeit not conclusively, in existing research. Across three samples (n = 720) we sought to compare preference ratings of 40 images that represented ten biomes (beach, lake, tropical and temperate forest, mars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
0
19
1
Order By: Relevance
“…There are three reasonable possibilities: the environments themselves are more conducive to well-being; different kinds of people frequent different kinds of environments; and some environments are more accessible. For example, Mangone et al [51] found dramatic differences in people's assessments of various narrower environment types (e.g., beaches vs. swamps); however, the most and least preferred biomes did not easily cleave into the green space vs. blue space categories, as one might intuit when considering beaches and swamps. The benefits of particular environments may further vary in ways that are more nuanced than our three categories could discover.…”
Section: Discussionmentioning
confidence: 99%
“…There are three reasonable possibilities: the environments themselves are more conducive to well-being; different kinds of people frequent different kinds of environments; and some environments are more accessible. For example, Mangone et al [51] found dramatic differences in people's assessments of various narrower environment types (e.g., beaches vs. swamps); however, the most and least preferred biomes did not easily cleave into the green space vs. blue space categories, as one might intuit when considering beaches and swamps. The benefits of particular environments may further vary in ways that are more nuanced than our three categories could discover.…”
Section: Discussionmentioning
confidence: 99%
“…Hartmann and Apaolaza-Ibáñez (2013) confirm the role of familiarity as there are preferences for images of lush green landscapes with water and familiar biomes (see also Mangone et al, 2021 ). Human nature attachment has been related to both evolution and cultural bonds to places, as landscape preferences are related to places where human beings feel safe and at home ( Adevi and Grahn, 2012 ).…”
Section: Fear and Preference Savanna Hypothesis And Prospect Refuge T...mentioning
confidence: 90%
“…Beside the prospect-refuge-theory and the Savanna Hypothesis, Kaplan’s landscape preference matrix theory ( Kaplan and Kaplan, 1989 ) and the stress recovery theory ( Ulrich et al, 1991 ) argue that humans prefer natural green environments. More importantly and in line with the concept of mosaic environments, in addition to the Savanna hypothesis, two other hypotheses with respect to the specific habitat where humans have evolved have been presented ( Han, 2007 ; Mangone et al, 2021 ). One option is the forest hypothesis, which argues that human evolution took place in closed, forested settings and the other one is the grassland–woodland hypothesis, which proposes that a mosaic of both settings was the adaptive environment for hominids.…”
Section: Fear and Preference Savanna Hypothesis And Prospect Refuge T...mentioning
confidence: 92%
See 1 more Smart Citation
“…This landscape includes water, potential game, and several natural hideouts, similar to African savannas where the evolution of man occurred [45][46][47][48][49]. Other evolutionary psychologists, in turn, challenge this thesis, believing that humans prefer landscapes that are a part of their habitat, or are familiar to them [50,51].…”
Section: Human Preferences In Experiencing and Evaluating Landscape Attractiveness And Their Sourcesmentioning
confidence: 99%